Implied market loss given default: Structural-model approach - Jakub Seidler (Charles University in Prague, Institute of Economic Studies (IES), 2008)
This paper focuses on the key credit risk parameter Loss Given Default (LGD). We describe its general properties and determinants with respect to seniority of debt, characteristics of debtors or macroeconomic conditions. Further, we illustrate how the LGD can be extracted from market observable information with help of the adjusted Mertonian structural approach. We present a derivation of the formula for expected LGD and show its sensitivity analysis with respect to other structural parameters of the company. Finally, we estimate the 5-year expected LGDs for companies listed on Prague Stock Exchange and find out, that the average LGD for this analyzed sample is around 20%. To the author's best knowledge, those are the first implied market estimates of LGD in the Czech Republic.
Keywords: C02; G13; G33; 330; loss given default; credit risk; structural models; Kreditrisiko; Kreditgeschäft; Risikomanagement; Tschechische Republik